Efficacy of Lobelia alsinoides Lam ethanolic extract on a third‐degree burn: An experimental study on rats - Samdavid Thanapaul, Rex Jeya Rajkumar; Ranjan, Abraham; Manikandan, Sreeraj K.; Nadar, M. S. A. Muthukumar (Dermatologic therapy, 2020)
This is the first study to evaluate the topical application of Lobelia alsinoides Lam (LT) ethanolic extract on burns in rats. A deep third‐degree burn wound was inflicted in adult male Wistar rats and the burns were dressed daily with a topical ointment formulation (Patent filed) comprising of Lobelia alsinoides Lam (5% and 10% w/w). The wound had noteworthy contraction and quicker eschar removal in 10% w/w LT‐treated groups followed by 5% w/w treated groups on comparing with the commonly prescribed ointment (SilverexTM containing 1% w/w Silver sulfadiazine). Histopathological analysis showed that ointment containing 10% w/w LT ethanolic extract significantly increased fibroblast growth, which plays a major role in anatomic integrity, collagen synthesis, and accelerated the rate of the healing process. This study shows that the ethanolic extract of Lobelia alsinoides Lam, a previously pharmacologically unreported traditional medicinal plant, possesses wound contraction and eschar removal properties on burn wounds.